1999
DOI: 10.1046/j.1469-8137.1999.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of ambient ozone on watermelon yield and physiology at a rural site in Eastern Spain

Abstract: The study reported was conducted to establish the impacts of photochemical oxidants (primarily ambient ozone, O $ ) on the yield of watermelon (Citrullus lanatus) at a site on the east coast of Spain. Fruit yield and quality were monitored in plots established in a commercial watermelon field exposed, in open-top chambers (OTCs), to nonfiltered air (NFA ; near-ambient levels of ozone) or charcoal-filtered air (decreased levels of photochemical oxidants including O $ ; CFA), or to ambient air (AA), durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 70 publications
4
37
0
Order By: Relevance
“…The same day the plants were transplanted into pots they were introduced in slightly modified NCLAN-type OTCs (see Gimeno et al, 1999). Three 0 3 treatments were used: charcoal filtered air (CFA) presenting subphytotoxic 0 3 levels, non-filtered air (NFA) with close to ambient 0 3 levels and non-filtered air supplemented with 40 ppb 0 3 from 07:00 to 17:00 (GMT) 5 days week" 1 (NFA + ).…”
Section: Ozone Treatmentsmentioning
confidence: 99%
“…The same day the plants were transplanted into pots they were introduced in slightly modified NCLAN-type OTCs (see Gimeno et al, 1999). Three 0 3 treatments were used: charcoal filtered air (CFA) presenting subphytotoxic 0 3 levels, non-filtered air (NFA) with close to ambient 0 3 levels and non-filtered air supplemented with 40 ppb 0 3 from 07:00 to 17:00 (GMT) 5 days week" 1 (NFA + ).…”
Section: Ozone Treatmentsmentioning
confidence: 99%
“…Oshima et al (1979) reported that exposure to ozone decreased boll production in cotton, although boll size and the proportions of boll components were unaffected. Similarly, the adverse effect of ozone on floral initiation reported for muskmelon and watermelon by Fernandez-Bayon et al (1993) reduced fruit numbers and yield (Gimeno et al, 1999). Numerous studies have shown that exposure frequently reduces yield in grain crops by decreasing ear and pod numbers, seed numbers per ear, spikelet or pod (and hence seed number per plant), and individual seed weight (Table 4).…”
Section: Effects On Seed and Fruit Yield And Yield Componentsmentioning
confidence: 89%
“…By contrast, Grunwald & Endress (1988) noted that the protein content of seeds was unaffected in soybean, but the oil content was reduced following exposure ; reductions in oil content have also been reported for oilseed rape (Bosac et al, 1998 ;. Decreases in soluble carbohydrate or solids have been noted for both grain (oilseed rape ; Bosac et al, 1998) and fruit crops (watermelon, Gimeno et al, 1989Gimeno et al, , 1990Gimeno et al, , 1999. In Lima bean (Phaseolus lunatus), exposure to ozone increased the concentrations of nitrogen and several essential amino acids in the seed (Meredith et al, 1986), while the calcium, magnesium, potassium and phosphorus content of the grain was increased in spring wheat (Fuhrer et al, 1990).…”
Section: Effects Of Ozone On Seed and Fruit Quality Germination And mentioning
confidence: 99%
See 1 more Smart Citation
“…High O 3 concentrations have long been known to affect many physiological and biochemical characteristics, as well as growth and yield of agricultural crops [4][5][6] and natural vegetation [7][8][9]. It is generally assumed that damage by O 3 is mainly the result of reactive oxygen species formation, promoting oxygen toxicity in the plant cell [10].…”
Section: Introductionmentioning
confidence: 99%